Cluster development programs in Ethiopia: Evidence and policy implications - Merima Ali; Olivier Godart; Holger Görg; Adnan Seric (Kiel Institute for the World Economy (IfW), 2016)
[Introduction] Cluster development programs have become increasingly widespread tools in fostering innovation and growth of a competitive private sector in developing countries, including Ethiopia. Naturally emerged clusters of micro- and small-scale enterprises (MSEs) are predominantly common in Ethiopia in traditional and labor intensive sectors in rural and poor urban areas. This has attracted the interest of policy-makers and various development organizations such as UNIDO to promote such clusters because of the direct impact they have on poverty. A cluster based development has also been given a top priority in the country's current five years Growth and Transformation Plan (GTP) as the main tool for spurring income and employment growth among MSEs. Owing to the existing policy enthusiasm to promote clusters, this report will pro-vide additional background information to assist the ongoing efforts by the government and UNIDO and highlight possible potential avenues for intervention and investment targeting. The report reviews the relevant literature on cluster development, discusses specific case study evidence for Ethiopia, and provides explorative evidence from more aggregate data on overall colocalization of enterprises in Ethiopia. More specifically, the report provides a general background on cluster development concept, the advantages of industrial clusters and the rationale for cluster development interventions in Section 2 and 3. A brief discussion of the MSE sector and clusters in Ethiopia is provided in Section 4. In Section 5, different past and ongoing cluster development programs in Ethiopia that are implemented both by UNIDO and the government are discussed. These programs will be presented in detail and lessons learnt will be drawn. In Section 6, we use more aggregate data to chart the localization of firms across different regions in Ethiopia to provide an overall picture of colocalization of firms across the country. We also present some evidence on characteristics of such locations, in terms of overall firm size, productivity, and linkages with the local economy. Section 7 summarizes the main findings of the report and provides some conclusions and policy recommendations for further integration of the cluster development methodology in to the national development processes.
Keywords: 330